Draft Third Five Year Plan Bihar Vol. II Statistical Appendices - Planning Commission (Planning Commission, 1960)
Summary Statement of Plan Outlay Proposed List of Schemes Carried Over From the Second Plan. List of New Schemes Proposed for Inclusion in the Third Plan. Agricultural Production Summary Statement of Plan Outlay Proposed. List of Schemes Carried Over From the Second Plan. List of New Schemes Proposed For Inclusion. Principal Protect Proposed in Draft State Plan Land Development Summary Statement on Plan Outlay Proposed Marketing Summary Statement of Plan Outlay Proposed Animal Husbandry Summary Statement of Plan Outlay Proposed.
Bihar